2021
DOI: 10.1108/ecam-01-2020-0075
|View full text |Cite
|
Sign up to set email alerts
|

Window geometry impact on a room's wind comfort

Abstract: PurposeNatural ventilation is an environmentally friendly effective way of improving thermal comfort and the quality of indoor conditions if applied properly. This study aims to investigate the physical mechanism of the air movement and also the influence of building geometry in a cross-ventilated room through a parametric study of window geometrical characteristics using computational fluid dynamics.Design/methodology/approachMomentum and continuity equations are solved by the control volume method using a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Similarly, Felimban et al (2019) found that due to the poor designs of windows, it led to a temperature above 238C. The relationship of studies (Fallahtafti and Mahdavinejad, 2021;Felimban et al, 2019) on energy consumption has been established by Yang et al (2023) as an inverse relationship between temperature and energy consumption. Moreover, their study found that an increase in room density, room locations and floor influenced electricity consumption.…”
Section: Pm 423mentioning
confidence: 97%
See 3 more Smart Citations
“…Similarly, Felimban et al (2019) found that due to the poor designs of windows, it led to a temperature above 238C. The relationship of studies (Fallahtafti and Mahdavinejad, 2021;Felimban et al, 2019) on energy consumption has been established by Yang et al (2023) as an inverse relationship between temperature and energy consumption. Moreover, their study found that an increase in room density, room locations and floor influenced electricity consumption.…”
Section: Pm 423mentioning
confidence: 97%
“…The relationship between thermal comfort and energy has provided diverse results among studies. Some schools of thought reported a positive relationship between thermal comfort and energy consumption (Wang et al ., 2021; Fallahtafti and Mahdavinejad, 2021). Others are of the view that the lack of sustainable building design shows a negative effect on energy use intensity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Form optimization is therefore a consistent research field: usual approaches include cost-evaluation, glazing properties, heat losses (Granadeiro et al, 2013). In this sense, many approaches are keeping into account geometry together with structural properties, in order to optimize use of materials, and to provide light structures (Beghini, Beghini, Katz, Baker, & Paulino, 2014;Rozvany, 2009;Sigmund, 2000), or considering solar radiation gain and efficiency (Fallahtafti, R., Mahdavinejad, 2015;Yi, H., Srinivasan, R.S., Braham, 2015;Yi, Y.K., Malkawi, 2012;Zhang, L., Zhang, L., Wang, 2016).…”
Section: Form and Structure Optimizationmentioning
confidence: 99%